The effects of combined aerobic and resistance training on heart rate variability in postmenopausal women - Rossi, Fabrício E. [UNESP]; Ricci-Vitor, Ana L. [UNESP]; Buonani, Camila S. [UNESP]; Vanderlei, Luiz C. M. [UNESP]; Freitas Jr., Ismael F. [UNESP] (My University, 2013)
Model of the study: Controlled clinical trial. Objective: To verify the effects of 16 weeks of combined aerobic and resistance training on cardiac autonomic modulation in menopausal women. Methods: 17 menopausal women were divided into two groups: the training group (TG: n=11) and control group (CG: n=6). The body composition variables were estimated using dual-energy X-ray absorptiometry. The cardiac autonomic modulation was evaluated by heart rate variability using linear indexes. The training protocol consisted of 16 weeks of 50 minutes of resistance training and 30 minutes of aerobic training. Results: For the TG there was an increase in the rMSSD(ms) index (pre:17,4±3,7 and post:24,8±13,1, p<0,045), an increase in the duration of the intervals between the cardiac beats(ms) (pre:891,2±80,2 and post:974,1±71,4, p<0,003) and in the values of heart rate(bpm) (pre:68,1±6,4 and post:62,0±4,7, p<0,003), additionally for the spectral indexes in normalized units, changes for LF (pre:52,2±13,1 and post:44,5±12,4, p<0,025) and HF (pre:47,8±13,3 and post:55,5±12,4, p<0,025) were noticed, demonstrating increased parasympathetic and reduced sympathetic. There were no significant differences to CG. Conclusion: combined aerobic and resistance training promoted benefits to the autonomic modulation in menopausal women.
Keywords: Aerobic training; Autonomic nervous system; Exercise; Parasympathetic nervous system; Postmenopausal; Resistance training; adult; aerobic exercise; aged; body composition; controlled clinical trial; controlled study; dual energy X ray absorptiometry; female; heart rate; heart rate variability; heart rhythm; human; postmenopause; resistance training